Remanufacturing on a Framework for Integrated Technology and Product-System Lifecycle Management (ITPSLM) - Guelere Filho, A.; Pigosso, D. C. A.; Ometto, A. R.; Rozenfeld, H. (Cranfield University Press, 2009)
In PSS context the product lifecycle needs to be managed in a holistic and structured way by using product life-cycle management (PLM) approach. The remanufacturing is an important strategy in this process, since the parts of a product that is being taken back at the end of its service can be remanufactured and new products send back to the market, fulfilling the needed functions. This paper aims to present a framework for ITPSLM composed by three business process (innovation management, technology development, productservice system development) and two support process (configuration management and business process management) and its relation to remanufacturing.
Organised by: Cranfield University
Keywords: Remanufacturing; Product-Service Systems; Eco-Innovation; Product Life-Cycle Management